Skewed X-Chromosome Inactivation and Compensatory Upregulation of Escape Genes Precludes Major Clinical Symptoms in a Female With a Large Xq Deletion - Santos-Rebouças, Cíntia B.; Boy, Raquel; Vianna, Evelyn Q.; Gonçalves, Andressa P.; Piergiorge, Rafael M.; Abdala, Bianca B.; dos Santos, Jussara M.; Calassara, Veluma; Machado, Filipe B.; Medina-Acosta, Enrique; Pimentel, Márcia M. G. (Frontiers in Genetics, 2020)
In mammalian females, X-chromosome inactivation (XCI) acts as a dosage compensation mechanism that equalizes X-linked genes expression between homo- and heterogametic sexes. However, approximately 12-23% of X-linked genes escape from XCI, being bi-allelic expressed. Herein, we report on genetic and functional data from an asymptomatic female of a Fragile X syndrome family, who harbors a large deletion on the X-chromosome. Array-CGH uncovered that the de novo, terminal, paternally originated 32 Mb deletion on Xq25-q28 spans 598 RefSeq genes, including escape and variable escape genes. Androgen receptor (AR) and retinitis pigmentosa 2 (RP2) methylation assays showed extreme skewed XCI ratios from both peripheral blood and buccal mucosa, silencing the abnormal X-chromosome. Surprisingly, transcriptome-wide analysis revealed that escape and variable escape genes spanning the deletion are mostly upregulated on the active X-chromosome, precluding major clinical/cognitive phenotypes in the female. Metaphase high count, hemizygosity concordance for microsatellite markers and monoallelic expression of genes within the deletion suggest the absence of mosaicism in both blood and buccal mucosa. Taken together, our data suggest that an additional protective gene-by-gene mechanism occurs at the transcriptional level in the active X-chromosome to counterbalance detrimental phenotype effects of large Xq deletions.